Acúmulo de macronutrientes por duas cultivares de cebola produzidas em sistema de semeadura direta - May, André; Filho, Arthur Bernardes Cecílio; Porto, Diego Resende de Queirós; Vargas, Pablo Forlan; Barbosa, José Carlos (FapUNIFESP (SciELO), 2008)
Economically, onion is the third more important vegetable in Brazil. As a consequence of the increasing by use of new hybrid varieties, the nutritional management of the crop needs to be adequately known. This research was carried out in São José do Rio Pardo, São Paulo State, Brazil, from March 7 to August 8, 2004. The objective was to quantify, under field conditions, the accumulation of macronutrients by onion cultivars established by direct sowing. The experimental design was in randomized blocks with three replicates. The cultivars studied were Optima and Superex. Samples were taken at 30, 50, 70, 90, 110, 130 and 150 days after sowing. With population of 354,000 plants ha -1 and productivity estimated in 64.8 t ha -1, 'Optima' extracted on 150 days after sowing: 78.77, 13.04, 75.77, 59.09, 11.70 and 24.38 kg ha -1 of N, P, K, Ca, Mg and S, respectively, and 'Superex', for the same plant population, and productivity at 72 t ha -1, 64.68, 10.33, 68.28, 65.58, 13.03 and 24.74 kg ha -1 of N, P, K, Ca, Mg and S, respectively. The Optima hybrid exported through its bulb about 49.17% of N, 60.60% of P, 61.16% of K, 41.15% of Ca, 43.56% of Mg, and 47.18 of S, the equivalent to 38.73, 7.90, 46.34, 24.32, 5.10 and 11.51 kg ha -1, respectively. The Superex hybrid exported through its bulb about 44.29% of N, 55.85% of P, 62.54% of K, 35.71% of Ca, 31.82% of Mg, and 48.80% of S, the equivalent to 28.65, 5.77, 42.70, 23.42, 4.15, and 12.07 kg ha -1, respectively.
Accumulation of macronutrients by two onion cultivars on direct sowing system
Keywords: Allium cepa L.; Fertilization; Nutrients; Plant population; accumulation; cultivar; experimental design; hybrid; nutrient uptake; sowing; vegetable; Brazil; Sao Jose do Rio Pardo; Sao Paulo [Brazil]; South America; Allium cepa; cultivation; plant